INFLUENCE OF HVOF COATING ON THE FATIGUE STRENGTH OF 15-5 PH STAINLESS STEEL - Voorwald, H. J. C. [UNESP]; Cioffi, M. O. H. [UNESP]; Junior, G. S. [UNESP]; Clark, G.; Wang, C. H. (Trans Tech Publications Ltd, 2014)
Structural component failures due to cyclic loading are associated to surface damage of materials and its interaction with environment. Fatigue failure occurs with stresses below the yield strength of each material and is a result of crack initiation and propagation. In aeronautical components is an important parameter to be considered in project, as well as the corrosion and wear resistance. Thermally sprayed HVOF coatings have been considered to replace galvanic chromium deposits with comparable performance for wear and corrosion resistance. The aim of present research is to study the influence of WC-13Co-4Cr applied by HVOF, on the axial fatigue strength of 15-5 PH stainless steel. The shot peening treatment was used to restore fatigue performance.
Keywords: 15-5PH; HVOF; Fatigue; Shot Peening